Diagnóstico de las instalaciones eléctricas del taller industrial tec-mec durante el período comprendido 2014. - Torres Ureña, Erwin Javier (2015)
In the present work describes the methodology of redesign of the electrical system the Industrial Workshop TEC-MEC, for which first proceeded to carry out the lifting of loads, and then assess the situation of the current installation and function to this propose a plan of improvements. On initial inspection is I can reveal that there was a lack of lighting and also an inadequate distribution of brakes for protections, and a correct distribution of the conductors for electrical outlets. Through the redesign was raised the calculation of conductor and protections of the general Board, as well as the redesign of the lighting system and the workshop strength, in addition the respective plans were developed. The proposed improvement will serve for that in the workshop there is a better distribution of the equipment and be able to have an environment of industrial safety.